(untitled) (American Journal of Medical Science and Innovation, 2024)
Ensuring high-quality healthcare services is crucial for the well-being of individuals and the overall development of societies. In Saudi Arabia, healthcare reform efforts under Vision 2030 emphasize the importance of enhancing healthcare service quality. One key aspect of these reforms is implementing the unified medical insurance system, NPHIES. This system aims to improve access to healthcare and enhance the quality of services provided. However, there is a lack of research examining the specific impact of NPHIES on healthcare service quality, particularly in hospitals like Arrawdha General Hospital in Dammam. This study aims to investigate the impact of NPHIES implementation on healthcare service quality at Arrawdha General Hospital in Dammam, Saudi Arabia. By examining the relationship between NPHIES and healthcare service quality, the study seeks to provide valuable insights that can inform healthcare policies and practices in the region. The study has adopted a quantitative approach, collecting data through a questionnaire administered to physicians and administrators at Arrawdha General Hospital. Statistical analysis (descriptive statistics, t-tests, ANOVA, and Pearson’s correlation coefficient) have been used to analyze the data. Statistical analysis showed no significant differences in NPHIES implementation or healthcare service quality based on demographics suggesting a consistent perception across different demographic groups. The study also identified a statistically significant positive effect of NPHIES on healthcare service quality, emphasizing its role in improving healthcare services. Future research should examine the impact of the Unified Medical Insurance System (NPHIES) implementation on elderly patient satisfaction and health outcomes in Saudi Arabia.